Community-Based Drug Prevention Outreach through Collaboration between Villages and the Pelalawan Regency National Narcotics Agency (BNNK Pelalawan) - Muhammad Hafizh Rahyunir; Muhammad Zulherawan (Nanggroe: Jurnal Pengabdian Cendikia, 2026)
Drug abuse in rural areas requires prevention strategies that emphasize not only enforcement measures but also strengthening the capacity of village governments and community participation. This community service program aims to improve the understanding of village officials and residents regarding the dangers of drugs, build collaboration with the Pelalawan Regency National Narcotics Agency (BNNK Pelalawan), and encourage the strengthening of village institutions through community-based prevention programs. The implementation methods include field observations, coordination with partners, outreach/socialization, assistance, monitoring and evaluation, and the preparation of activity outputs as outlined in the proposal and reported in the implementation progress. The results of the program indicate an increase in participants’ understanding of types of drugs, the impacts of drug abuse, early detection, and reporting mechanisms, along with strengthened cooperation networks between the village government and BNNK Pelalawan. The program also produced outputs in the form of community service articles, educational media such as leaflets, posters, handouts, videos, and media publications as a means of disseminating results. The main impact of this activity is the growth of collective awareness within the village community and the increased institutional readiness of village governments in developing sustainable drug prevention programs.